The social science of offshore aquaculture: uncertainties, challenges and solution-oriented governance needs - Krause, Gesche; Weitzman, Jenny; Rector, Megan E.; Filgueira, Ramon; Burg, Sander van den; Dankel, Dorothy Jane; Olsen, Marit Schei; Osmundsen, Tonje C. (Frontiers in Aquaculture, 2024)
Aquaculture technology is on the move, enabling production in more open and exposed ocean environments around the world. These new systems offer solutions to environmental challenges facing conventional aquaculture, yet new technologies also create new social challenges while potentially exacerbating, or at minimum recreating, others. Offshore aquaculture research and governance are still in early stages, as is our understanding of the social repercussions and challenges associated with development. This paper provides an evaluation and reflection on offshore aquaculture from a social science perspective and is based on findings from a modified World Café group discussion method including the thoughts and experiences of social science experts. Key challenges and uncertainties including a lack of an appropriate regulatory framework, societal perceptions of offshore aquaculture, and offshore aquaculture's contribution to society were identified. The governance implications of these challenges are discussed as well as the need for social sciences to address these challenges through transformative and transdisciplinary approaches that bridge science and society.